A Novel Tunable Triple-Band Left-Handed Metamaterial - Si Li; Atef Z. Elsherbeni; Wenhua Yu; Wenxing Li; Yunlong Mao (International Journal of Antennas and Propagation)
A novel tunable triple-band left-handed metamaterial (LHM) composed of a single-loop resonator (SLR) and a variable capacitor-loaded short wire pair (CL-SWP) printed on both sides of a substrate is presented in this paper. The CL-SWP-based metamaterial (MTM) is a novel single-sided LHM. It is theoretically analyzed capable of extracting tunable negative permeability and a wide-band negative permittivity. We ran simulations for the CL-SWP-based MTM, the SLR-based MTM, and the proposed LHM. Together with the measured results, it is identified that this novel LHM exhibits a tunable triple-band left-handed (LH) property. With the increase of the loaded capacitance, one LH band is relatively stable, while the other two are moving towards lower frequencies with their bandwidth getting wider and narrower, respectively. The surface current density distributions indicate that the first LH band is mainly decided by the SLR, one of the rest 2 LH bands is mainly decided by the CL-SWP, and the other one is decided by the SLR and CL-SWP together.